¿“Arab Spring” or imperial reconfiguration? Hopes and limits of social mobilization in the Middle East - Gaussens, Pierre (2011)
This article defends the need to overcome the media version of the “Arab Spring”. The author proposes a sociological approach to the phenomena of social mobilization currently underway in the Middle East. The article uncovers the opposing social and imperialist logics that structure the political power relations in the region and that determine the reach of the processes of social transformation.